2019
DOI: 10.1142/s0218625x18501937
|View full text |Cite
|
Sign up to set email alerts
|

PLASMA PRETREATMENT ON TASAR SILK FABRICS COATED WITH ZnO NANOPARTICLES AGAINST ANTIBACTERIAL ACTIVITY

Abstract: Plasma pretreatment is an eco-friendly process employed to modify the surface properties and improve the adhesion properties of tasar silk fabrics. The plasma pretreatment has been carried out in DC glow discharge plasma at constant power and for different treatment durations (5, 10 and 30[Formula: see text]min). ZnO nanoparticles (ZnO NPs) play a significant role in antibacterial, cleaning and UV protection. ZnO NPs have been synthesized by the wet chemical method and the average crystallite size of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Contact angle measurement clearly shows that the hydrophobic nature of coated fabrics can be increased with plasma pretreatment. SEM analysis shows the improvement of the adsorption on plasma treated fabric and EDS shows the presence of ZnO (61) . The antibacterial activity and thermal stability improve significantly after plasma pretreatment.…”
Section: Plasma Pretreatment On Tasar Silk Fabrics Coated With Zno Nanoparticles Against Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Contact angle measurement clearly shows that the hydrophobic nature of coated fabrics can be increased with plasma pretreatment. SEM analysis shows the improvement of the adsorption on plasma treated fabric and EDS shows the presence of ZnO (61) . The antibacterial activity and thermal stability improve significantly after plasma pretreatment.…”
Section: Plasma Pretreatment On Tasar Silk Fabrics Coated With Zno Nanoparticles Against Antibacterial Activitymentioning
confidence: 99%
“…The improved surface property in terms of hydrophobicity is analyzed by using a contact angle test. It is found that the plasma pretreated silk fabrics coated with ZnO NPs have better antibacterial activities against Escherichia Coli bacteria (61) . ZnO coated and plasma pretreated silk fabrics showed excellent antibacterial activity against E. Coli bacteria.…”
Section: Plasma Pretreatment On Tasar Silk Fabrics Coated With Zno Nanoparticles Against Antibacterial Activitymentioning
confidence: 99%
“…Nanomaterials have been used for antibacterial finishing of textiles, due to their stability and effectiveness. 18 Silver and zinc oxide (ZnO) nanoparticles were coated onto cotton fabric by heat treatment, exhibiting good antibacterial property. 19 Silk fabrics were also treated with AgNPs, which imparted antibacterial activity to silk fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Since silk is a type of protein, it is easy for microorganisms and bacteria to accumulate and proliferate on silk fibers in a humid environment [ 10 , 11 ], which can cause damage to fibers in the silk products and even bring about skin diseases. Many antibacterial agents have been applied to eliminate microbial damage to natural fibers [ 12 , 13 ]. Compared with organic reagents, inorganic nanomaterials, especially PtNPs, are stable and effective for antimicrobial applications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many antibacterial agents have been applied to eliminate microbial damage to natural fibers [ 12 , 13 ]. Compared with organic reagents, inorganic nanomaterials, especially PtNPs, are stable and effective for antimicrobial applications [ 12 ]. PtNPs have high activity [ 14 , 15 ] and selectivity for catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%